HUBUNGAN KARAKTERISTIK INDIVIDU DENGAN PRAKTIK KADER JUMANTIK DALAM PSN DBD DI KELURAHAN SAMPANGAN SEMARANG - Rezania, Nurul; Handayani, Oktia Woro Kasmini (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2015)
The purpose of this study was to determine the relationship between the characteristics of individuals with jumantik cadres practices in dengue PSN in the Sampangan Village. This research is explanatory research using cross sectional design. Samples numbered 49 in the RT-level cadres jumantik Urban Village Sampangan taken with samples Total Samples techniques. The instrument used was a questionnaire sheet and statement of village resident. Data were analyzed using Chi square test and Fisher's exact test. The results showed that variables relationship is long task (p value = 0.012). There were no relationship between variables age (p value = 0.665), education level (p value = 0.492), employment status (p value = 0.287), per capita family income (p value = 1), how to become a cadre of (p value = 0.278), training (p value = 0.760), and knowledge (p value = 0.363). Suggestions is to improve coordination and regular meetings with the cadre of jumantic for healthy center, give reward for jumantic of cadre for healthy service.